Metagenomic next-generation sequencing provides prognostic warning by identifying mixed infections in nocardiosis - Jiao, Mengfan; Ma, Xiaoxu; Li, Yaoguang; Wang, Huifen; Liu, Ying; Guo, Wenhu; Lv, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Nocardia is an opportunistic pathogen that mainly involves immunosuppressed patients and causes a high mortality rate. As an emerging approach to detect infectious pathogens, metagenomic next-generation sequencing (mNGS) was reported in the detection of Nocardia. However, there is no evidence demonstrating the effect of mNGS on the prognosis of Nocardia infection. In this retrospective study, we included 18 nocardiosis patients. Nocardia species were detected by mNGS from their clinical samples. All the patients were diagnosed with nocardiosis by clinical experts through a comprehensive evaluation. Of these 18 patients, fever is the most frequent initial symptom. Compared to traditional culture methods, mNGS provides a faster turnaround time (TAT) and higher sensitivity. Pulmonary nocardiosis was the most common clinical presentation in the study. mNGS detected 13 types of Nocardia species, of which Nocardia abscessus and Nocardia cyriacigeorgica were the most common species. The study's most noteworthy discovery is that mNGS outperforms culture at detecting mixed infections (more than one pathogen detected in one clinical specimen, including bacteria, fungi, and excluding virus), and number of infectious species was an independent risk factor for nocardiosis patients’ prognostics after adjusting age, ICU days, gender and underlying diseases (adjusted HR = 1.47, 95% CI: 1.09-1.98, p = 0.011). As a result, we believe that by detecting mixed infections (more than one pathogenic species), mNGS can provide a clinical risk warning for the prognosis of nocardiosis.